2003
DOI: 10.1074/jbc.m211097200
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of O-Glycan Synthesis in IgA1 Hinge Region Is Determined by a Single Enzyme, UDP-N-Acetyl-α-d-galactosamine:PolypeptideN-Acetylgalactosaminyltransferase 2

Abstract: The hinge region of human immunoglobulin A1 (*IgA1) possesses multiple O-glycans, of which synthesis is initiated by the addition of GalNAc to serine or threonine through the activity of UDP-N-acetyl-␣-D-galactosamine:polypeptide N-acetylgalactosaminyltransferases (pp-GalNAc-Ts). We found that six pp-GalNAc-Ts, ppGalNAc-T1, -T2, -T3, -T4, -T6, and -T9, were expressed in B cells, IgA-bearing B cells, and NCI-H929 IgA myeloma cells. pp-GalNAc-T activities of these six enzymes for a synthetic IgA hinge peptide, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 56 publications
5
71
1
1
Order By: Relevance
“…10,11 The attachment of GalNAc to serine or threonine is catalyzed by UDP-N-acetylgalactosaminyl transferases (GalNAcT); a study in human B cells reported that among the six GalNAcTs expressed in these cells, GalNAcT2 exhibited the highest catalytic activity in transferring GalNAc to a synthetic peptide corresponding to the hinge region of human IgA1. 26 In agreement with this finding, our ongoing analysis showed approximately eightfold higher levels of GalNAcT2 mRNA in 6-19 transfectomas than in 46-42 hybridoma cells. Using these two IgA-secreting cells to modulate the expression of GalNAcT2, we should be able to formally prove that GalNAcT2 is indeed the enzyme responsible for the initiation of O-glycosylation of the hinge region of mouse IgA.…”
Section: Discussionsupporting
confidence: 75%
“…10,11 The attachment of GalNAc to serine or threonine is catalyzed by UDP-N-acetylgalactosaminyl transferases (GalNAcT); a study in human B cells reported that among the six GalNAcTs expressed in these cells, GalNAcT2 exhibited the highest catalytic activity in transferring GalNAc to a synthetic peptide corresponding to the hinge region of human IgA1. 26 In agreement with this finding, our ongoing analysis showed approximately eightfold higher levels of GalNAcT2 mRNA in 6-19 transfectomas than in 46-42 hybridoma cells. Using these two IgA-secreting cells to modulate the expression of GalNAcT2, we should be able to formally prove that GalNAcT2 is indeed the enzyme responsible for the initiation of O-glycosylation of the hinge region of mouse IgA.…”
Section: Discussionsupporting
confidence: 75%
“…The initial event is the addition of GalNac to threonine or serine in the protein backbone, mediated by a UDP-N-acetyl-␣-d-galactosamine:polypeptide N-acetylgalactosaminyltransferase (pp-GalNAc-Ts). A family of these enzymes has been described, only one of which, named pp-GalNAc-T2, seems to have significant function in human IgA1 B cells (26); IgD B cells have not been studied in this regard. The galactosylation of the core 1 structure then is completed by a core 1 ␤1 to 3 galactosyltransferase, C1Gal-T1 (25).…”
Section: Discussionmentioning
confidence: 99%
“…sites (73). Although there is a clear site preference, the enzyme is capable of adding GalNAc to all potential sites in IgA1 HR.…”
Section: Iga1 O-glycosylation Sites Identified By Ft-icr Msmentioning
confidence: 99%